2008
DOI: 10.1007/s11248-008-9205-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunogenicity and protective efficacy in mice of transgenic rice plants producing a vaccine candidate antigen (As16) of Ascaris suum fused with cholera toxin B subunit

Abstract: Cereal crops such as maize and rice are considered attractive for vaccine production and oral delivery. Here, we evaluated the rice Oryza sativa for production of As16-an antigen protective against the roundworm Ascaris suum. The antigen was produced as a chimeric protein fused with cholera toxin B subunit (CTB), and its expression level in the endosperm reached 50 microg/g seed. Feeding the transgenic (Tg) rice seeds to mice elicited an As16-specific serum antibody response when administered in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In fact, edible vaccines produced in papaya and corn seed induced protection against porcine-cysticercosis (70-90%) and porcine-transmissible gastroenteritis virus (50%) [76,77]. Even more, edible vaccines can include adjuvants as it was the case for As16-an antigen protective against the roundworm Ascaris suum fused with CTB in transgenic rice seeds, resulting in an antibody response [78].…”
Section: Plant-based Veterinary Vaccinementioning
confidence: 99%
“…In fact, edible vaccines produced in papaya and corn seed induced protection against porcine-cysticercosis (70-90%) and porcine-transmissible gastroenteritis virus (50%) [76,77]. Even more, edible vaccines can include adjuvants as it was the case for As16-an antigen protective against the roundworm Ascaris suum fused with CTB in transgenic rice seeds, resulting in an antibody response [78].…”
Section: Plant-based Veterinary Vaccinementioning
confidence: 99%
“…Ascaris suum infects pigs (but not humans), resulting in a decrease in daily weight gain and an increase in feed-to-gain ratio, resulting in economic losses (Stewart and Hale 1988). Matsumoto et al (2009) produced a 16-kDa protein of A. suum (As16) fused with CTB in transgenic rice seeds, and demonstrated that oral immunization with the chimeric protein together with mucosal CT adjuvant induced As16-specific serum IgG antibodies and reduced the number of larvae in the lungs after infection with A. suum embryonated eggs. Human roundworm, Ascaris lumbricoides, has a protein identical to A. suum As16 (Tsuji et al 2003).…”
Section: Matsumoto Et Al (2009) Reported a New Rice-based Vaccine Agmentioning
confidence: 99%
“…Tomato was tested as an edible vaccine against malaria (Chowdhury and Bagasra 2007 ), lettuce against the E. coli heat-labile toxin B subunit (Martínez-González et al 2011 ), rice against the roundworm Ascaris suum (Matsumoto et al 2009 ). Dorokhov et al ( 2007 ) A complete review about plant-made vaccines was published by Awale et al ( 2012 ).…”
Section: Vaccinesmentioning
confidence: 99%